THE IMPACT OF PREVENTIVE MEASURES ON GIARDIASIS MORBIDITY AMONG CHILDREN AND ADULTS FOR THE PERIOD 2010-2014 YEARS IN IVANO-FRANKIVSK - Мізюк, М. І.; Погорілий, М. П.; Суслик, З. Б.; Йонда, М. Є.; Мищенко, І. А.; Мізюк, Р. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
High prevalence of giardiasis among population needs effective preventive measures. Urbanization, migration of population, hygienic training and education influence on the parasitological situation. With the purpose of hygienic education of population in kindergartens of various Ivano-Frankivsk’s locations during 2009-2011 years anonymous questionnaire of parents was conducted. On the base of parasitological situation studying risk groups by physiological and occupational signs were formed. Annual survey of risk groups allowed to organize the medical examination for giardiasis, to use state funds and efficiency of medical prophylactic institutions more rationally. According to the obtained results of questionnaire the educational program of sanitary minimum for decreed contingents was improved. Annual dictations and written transfers about contact parasitoses were conducted for secondary school pupils. Healthy lifestyle, formation of stable skills for primary prevention of diseases were as a basis of preventive activity. As a result of the preventive measures the giardiasis morbidity was decreased among all contingents of population.